Food prices and inflation in developing Asia is poverty reduction coming to an end? (Asian Development Bank, 2008)
"The recent spike in global food prices and the short-sighted policy responses that accentuate volatility in prices threaten to push large numbers of people back below the poverty line--including many millions in developing Asia. Structural forces augmented by adverse cyclical events have put food prices on an upward trajectory that will not end soon. Unless trade is kept open and relative prices are allowed to reflect market scarcity, severe consequences will emerge. In the immediate future, carefully targeted assistance to the poor will be essential--both in terms of food and inputs necessary to increase food production in the coming crop season. A reevaluation of investment priorities and feasibility of agricultural projects must be undertaken in light of these price developments, accompanied by stronger efforts to boost agricultural productivity growth in order to mitigate any longer-term rise in food prices."--Abstract.